Analisis Asuhan Keperawatan Melalui Intervensi Kompres Bawang Merah Pada A.n J dan An. N Dengan Febris - Erda Agus Banapon (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2023)
ABSTRACT A NURSING CARE ANALYSIS THROUGH A RED ONION COMPRESS INTERVENTION IN PATIENTS AN. J AND AN. N WITH FEBRIS (FEVER) MEDICAL DIAGNOSIS AT RT 02 KEMIRI MUKA VILLAGE, DEPOK CITY Background: Fever or febris is a condition where body temperature rises above normal. Fever is not a disease itself, but it is a symptom of an underlying condition that needs to be treated properly to minimize the negative impacts. One of non-pharmacological interventions to treat fever, such as applying red onion compress, can be used for children. Objective: To analyze nursing care through a red onion compress intervention in patients AN. J and AN. N diagnosed with febris in the Kemiri Muka Village area, Depok City. Implementation: The nursing care for both patients was carried out from July 20th-22nd 2023, and from July 24th-26th 2023. The implementation focused on nursing diagnosis of hyperthermia, with the goal of reducing fever in both patients through the application of red onion compress. Results: The nursing evaluation of the main problem, hyperthermia, showed that after appliying the red onion compress to both patients for 3 days, the data showed a decrease in body temperature on the 3rd day after the nursing intervention. Conclusion and Recommendation: Red onion compress therapy proved to be effective in reducing body temperature in children with a nursing problem of hyperthermia. It is hoped that patients and/or families can apply this nursing intervention by applying red onion compress on the other family members who experience fever in order to reduce their body temperature. However, it is also important to pay attention to skin reactions after applying the red onion compress. Keywords: Febris, Hyperthermia, Red Onion Compress Intervention.